PROBLEMATIKA PEMBINAAN DAN PENGAWASAN PENGELOLAAN DANA DESA DI KABUPATEN MAGELANG - Yudhihana, Awang; Suranto, Suranto (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
This article aims to knowing problematics guidance and supervision of management of village funds in magelang regency. This article is included in the type of empirical legal research that has character is descriptive and uses a qualitative approach. In this study the source of the data obtained is the primary data source, which is based on the results of direct interviews with related sources, namely the Magelang District Society and Village Empowerment Service and Magelang District Inspectorate. Apart from primary data, it is also based on secondary data with library research. Based on the results of the research, it can be concluded that, the Government of Magelang Regency in carrying out the guidance and supervision of the management of village funds has been running quite well and has been in accordance with the applicable laws and regulations. However based on the results of the research, there are still problems that arise in the guidance and supervision of village fund management in Magelang Regency